The book of tomorrow a novel - Ahern, Cecelia 1981- (New York, NY Harper, 2011)
Forced into a humbler life with relatives in Ireland after the sudden death of her father, spoiled sixteen-year-old Tamara Goodwin discovers a diary of future entries written in her handwriting that she hopes will reveal the truth about her mother's troubling health
"Originally published in 2009 in Great Britain, in a slightly different form, by HarperCollins UK."
1
Keywords: Children of the rich -- Ireland -- Fiction; Fatherless families -- Ireland -- Fiction